Reclaiming the memory of pioneer female geologists 1800–1929 - A. Vincent (Advances in Geosciences, 2020)
Female earth scientists existed in the 19th century and the beginning of the 20th century in a number exceeding what we generally imagine. In this paper I present information on 210 of them who were active from 1800 to 1929. These women often overcame great challenges to achieve their positions, sometimes only to have their work attributed to men they worked with or for. Gender discrimination made access to university difficult and access to scientific careers even harder. They found several ways to overcome these difficulties thanks to the support of their parents or to the more ambiguous support of husbands or academic male mentors, through staying single, and through teamwork and mentorship with other women. In the same way many past female artists have been recently rediscovered, women scientists are progressively being saved from the dustbin of history, a huge task that has already been undertaken by several researchers. In addition to the review of their research, a fresh contribution to this collective work in progress is made with the presentation of hydrogeologist Norah Dowell Stearns. Finally, some reflections and suggestions are included on how we could fight this oblivion to which their work, their personalities and modern research on them are subject to.